Method for preparing zirconia toughened alumina zta ceramic by low temperature sintering and product thereof

CN119430969BActive Publication Date: 2026-10-27HEFEI CEMENT RESEARCH AND DESIGN INSTITUTE CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411720520.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2026-10-27
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

目前,ZTA陶瓷制备过程中加入的助烧剂主要为氧化物如MgO、TiO2、Cr2O3等,其原理是在烧结温度下,助烧剂中的阳离子通过扩散进入ZTA陶瓷晶格,与Al3+、Zr4+之间发生置换固溶,使晶格产生缺陷,降低烧结活化能,从而促进ZTA陶瓷烧结,但是由于Al3+、Zr4+均为高价的阳离子,受阴离子的静电吸引力较强,在低温下很难被烧结助剂中的阳离子置换,因此ZTA陶瓷的烧结温度都较高,一般都在1500℃以上,这极大的增加了ZTA陶瓷的生产成本

Benefits of technology

[0017]在本发明的工艺下,在ZTA陶瓷的烧结过程中,一方面助烧剂中的部分阳离子通过置换效应进入ZTA陶瓷晶粒晶格,提高ZTA陶瓷的烧结活性;另一方面通过熔解析出效应,ZTA陶瓷中的部分氧化铝和氧化锆组分一边溶解于粘流态的ZTA陶瓷助烧剂中一边又在易析出的位置析出氧化铝和氧化锆晶体,实现氧化铝和氧化锆的快速扩散,促进ZTA陶瓷在低烧结温度下快速致密化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430969B_ABST
    Figure CN119430969B_ABST
Patent Text Reader

Abstract

This invention relates to the field of engineering ceramic materials technology, specifically a method for preparing zirconia-toughened alumina (ZTA) ceramics using a low-temperature sintering process. The method includes preparing a ZTA ceramic sintering aid and a dry-pressed ZTA ceramic material, followed by molding, drying, and sintering the dry-pressed material at 1200-1300℃. The sintering aid is prepared from boric acid, sodium carbonate, potassium carbonate, calcium fluoride, bismuth trioxide, ammonium dihydrogen phosphate, antimony trioxide, and silicon dioxide in a specific ratio. The ZTA ceramic can achieve dense sintering at 1250-1300℃. After sintering, the main crystalline phase in the ZTA ceramic is the same as that of traditional ZTA ceramics sintered at high temperatures without the sintering aid, both being α-Al₂O₃ phase and tetragonal zirconia (…). t ZrO2) phase and monoclinic zirconium oxide ( m The ZTA ceramic prepared by the process of this invention has a density of 97.8% and a flexural strength of 478 MPa after sintering at 1250℃.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of engineering ceramic materials technology, specifically a method and product for preparing zirconia-toughened alumina (ZTA) ceramics by low-temperature sintering. Background Technology

[0002] ZrO2 ceramic oxygen is a commonly used ceramic reinforcement in engineering structural ceramics and iron-based composite wear-resistant materials due to its low price, simple production process, excellent mechanical properties, good wear and corrosion resistance, stable high-temperature performance, and high fracture toughness. Currently, ZrO2 ceramics are prepared by uniformly mixing ZrO2 powder, Al2O3 powder, Y2O3 powder, and a small amount of sintering aid powder, pressing them into shape, and then sintering at high temperature to obtain dense ZrO2 ceramics. Currently, the sintering aids added during the ZrO2 ceramic preparation process are mainly oxides such as MgO, TiO2, and Cr2O3. The principle is that at the sintering temperature, the cations in the sintering aid diffuse into the ZrO2 ceramic lattice and react with Al... 3+ Zr 4+ Substitutional solid solution occurs between the crystals, creating lattice defects and lowering the sintering activation energy, thereby promoting the sintering of ZTA ceramics. However, due to Al... 3+ Zr 4+ All ZTA ceramics are high-valence cations, strongly attracted by the electrostatic attraction of anions, making them difficult to replace with cations in sintering aids at low temperatures. Therefore, the sintering temperature of ZTA ceramics is generally high, typically above 1500℃, which significantly increases the production cost. Developing a highly active sintering aid and its preparation process for ZTA ceramic production would allow it to promote ceramic crystal growth at lower temperatures, assist in eliminating pores in ceramic particles, and achieve densification of ZTA ceramics. This would be of great significance in reducing the production cost of ZTA ceramics. Summary of the Invention

[0003] The purpose of this invention is to provide a method and product for preparing zirconia-toughened alumina (ZTA) ceramics using a low-temperature sintering process. Considering the formulation design of ZTA ceramic sintering aids, a glassy phase ZTA ceramic sintering aid has been developed. At lower sintering temperatures, the ZTA ceramic sintering aid between ZTA ceramic particles softens and becomes a viscous flow state. On one hand, the cations in the ZTA ceramic sintering aid enter the ZTA ceramic grain lattice through a substitution effect, improving the sintering activity of the ZTA ceramic. On the other hand, through a melting and precipitating effect, some alumina and zirconia in the ZTA ceramic dissolve in the sintering aid while simultaneously precipitating at easily precipitated locations, achieving rapid diffusion of alumina and zirconia and promoting rapid densification of the ZTA ceramic at low sintering temperatures.

[0004] The technical solution of this invention is as follows: A method for preparing zirconia-toughened alumina (ZTA) ceramics by low-temperature sintering, characterized by comprising the following steps: S1: Preparation of ZTA ceramic sintering aid S11: ZTA ceramic sintering aid, its raw material weight percentage formula is as follows: Boric acid 10%-15% Sodium carbonate 8-12% Potassium carbonate 4-6% Calcium fluoride 2-3% 6-8% bismuth trioxide 4-5% ammonium dihydrogen phosphate Antimony trioxide 5-7% 48%-59% silicon dioxide The total of all raw materials in the formula is 100%; S12: Ball mill the weighed raw materials to obtain ZTA ceramic sintering aid smelting raw materials; S13: Heat the ZTA ceramic sintering aid raw material to 1500-1550℃ and hold it at that temperature, then quench it in water, ball mill it, and sieve it to obtain the ZTA ceramic sintering aid; S2: Preparation of ZTA ceramic dry-pressed material S21: ZTA ceramic dry pressing material, its raw material weight percentage formula is as follows: Alumina micro powder 60%-90% Yttrium-stabilized zirconia micro powder 5%-38% ZTA ceramic sintering aid 2%-5% The total of all raw materials in the formula is 100%; S22: Weigh each raw material according to the formula ratio, ball mill it to obtain powder, add binder and mix to obtain ZTA ceramic dry pressing material; S3: Forming and Drying of ZTA Ceramics ZTA ceramic dry-pressed material is placed in a mold, pressed into a blank, and then dried; S4: Sintering of ZTA ceramics ZTA ceramic blanks are obtained by sintering at 1200-1300℃.

[0005] In step S11, the ZTA ceramic sintering aid has the following raw material weight percentage formulation: Boric acid (chemically pure) 10%-15% Sodium carbonate (chemically pure) 9% Potassium carbonate (chemically pure) 5% Calcium fluoride (chemically pure) 2-3% Bismuth trioxide (chemically pure) 155, Zirconium 160, 6-8% Ammonium dihydrogen phosphate (chemically pure) 4-5% Antimony trioxide (chemically pure) 141, Aluminum 143, 5-7% Silica (chemically pure) 48%-59%.

[0006] S12 includes the following steps; Pour the weighed raw materials into a corundum ball milling jar, add zirconia balls with a diameter of 30 mm at a ball-to-material mass ratio of 1-3:1, and set the ball milling jar to rotate at a speed of 60-100 r / min. After milling the raw materials for 60-120 min, remove them to obtain ZTA ceramic sintering aid smelting raw materials.

[0007] S13 includes the following steps: The platinum crucible furnace is heated to 1000-1050℃ at a rate of 3-4℃ / min. The mixed smelting raw material powder is poured in. When the furnace temperature rises again to 900-1000℃, it is held for 0.5-1h. Then, the temperature is raised to 1500-1550℃ at a rate of 3-4℃ / min and held for 1-2h. The molten material is then allowed to flow into water for water quenching. The glass fragments after water quenching are collected and placed in a planetary ball mill for ball milling. After ball milling for 12-16h, the slurry is poured out, dried, and sieved to obtain ZTA ceramic sintering aid.

[0008] In step S21, the weight percentage formula of ZTA ceramic dry pressing material is as follows: Alumina micro powder diameter 1-5μm 60%-90% Yttrium-stabilized zirconia micropowder, diameter 1-5 μm, 5%-38% ZTA ceramic sintering aid 2%-5% S22 includes the following steps: After weighing each raw material according to the formula ratio, use ethanol as solvent and ZrO2 grinding balls as grinding media to mix the materials in a planetary ball mill for 1-3 hours. After ball milling, dry the powder and then add 5-7 wt% of the powder's binder, polyvinyl alcohol (PVA) aqueous solution, and mix for 1-2 hours. After the mixed powder is sealed in a sealed bag and left to stand for 24-48 hours, it is sieved to obtain ZTA ceramic dry pressing material.

[0009] S3 includes the following steps: Select a mold, weigh out ZTA ceramic dry pressing material, put it into the mold, apply pressure to form, when the forming pressure reaches 100-120MPa, hold the pressure for 2-3 minutes, release the pressure, demold, place the formed ZTA ceramic green body at room temperature for 24-48 hours, and then put it in an oven at 50-80℃ to dry for 6-24 hours.

[0010] S4 includes the following steps: Place the ZTA ceramic blank in the sintering furnace and heat it to 400℃-450℃ at a rate of 2-3℃ / min, hold for 1-2 hours, then heat it to 500℃-550℃ at a rate of 1-2℃ / min, hold for 1-2 hours, then heat it to 1050℃-1100℃ at a rate of 3-4℃ / min, hold for 0.5-1 hours, then heat it to 1200-1300℃ at a rate of 2-3℃ / min, hold for 2-6 hours, and then turn off the furnace. The ZTA ceramic is then allowed to cool naturally in the furnace. When the temperature is below 70℃, the ZTA ceramic is removed from the furnace to obtain the sintered ZTA ceramic product.

[0011] Ceramic products are made using the methods described above.

[0012] The present invention will be further explained below: Preparation of ZTA ceramic sintering aid: At the glass melting temperature, boric acid is converted to boron trioxide, sodium carbonate to sodium oxide, potassium carbonate to potassium oxide, and ammonium dihydrogen phosphate to phosphorus pentoxide. At the melting temperature, sodium oxide and potassium oxide provide "free oxygen" to the layered boron trioxide, transforming the "boron-oxygen trigonal" into a "boron-oxygen tetrahedron," which combines with the silicon-oxygen tetrahedrons provided by silicon dioxide to form the main structure of the glass network. Simultaneously, phosphorus pentoxide converted from ammonium dihydrogen phosphate and bismuth trioxide also participate in the formation of the glass network. Antimony trioxide exists as a glass intermediate, and calcium fluoride exists as a glass modifier in the ZTA ceramic sintering aid. The sintering aid after water quenching after melting is a pure glass phase. See [link to relevant documentation]. Figure 1 .

[0013] Preparation of ZTA ceramic dry pressing material: The raw materials used are yttrium-stabilized zirconia micro powder, mainly yttrium-stabilized zirconia micro powder. During the sintering process of ZTA ceramics, yttrium oxide will inhibit the phase transformation of zirconia and improve the mechanical properties of ZTA ceramics. After the raw materials are ball-milled and mixed evenly, PVA solution is added to the dry pressing material as a temporary binder to facilitate the subsequent dry pressing of ZTA ceramics.

[0014] Forming and drying of ZTA ceramics: After forming under pressure of 100-120MPa, the ZTA ceramic green body is placed on a SiC oven plate and left at room temperature for 24-48 hours. Then, it is left at room temperature for an extended period of time to slowly remove some of the moisture from the ZTA ceramic green body, preventing cracking caused by excessive dehydration. The ZTA ceramic green body is then placed in a 70℃ oven for 6-24 hours to completely remove moisture, preparing it for sintering.

[0015] Sintering of ZTA ceramics: The ZTA ceramic plate is placed in the sintering furnace and heated to 400℃ at a rate of 2-3℃ / min. At this temperature, the temporary binder PVA has not yet decomposed, and the green body has a certain strength, so the heating rate is relatively fast. Hold at 400℃ for 1-2 hours to ensure uniform temperature inside and outside the green body. Then, heat to 500℃ at a rate of 1-2℃ / min. At this temperature, the temporary binder PVA begins to decompose, so the heating rate is slower to prevent the gases produced by PVA decomposition from causing cracking of the ZTA green body. Hold at 500℃ for 1-2 hours to ensure complete decomposition of PVA in the ZTA green body. Then, heat to 1100℃ at a rate of 3-4℃ / min and hold for 0.5-1 hour to ensure uniform temperature inside and outside the ZTA green body, preparing for final sintering. The temperature is then increased to 1200-1300℃ at a rate of 2-3℃ / min and held for 2-6 hours. At this sintering temperature, the ZTA ceramic sintering aid in the ZTA ceramic becomes viscous. The Na2O and K2O components in it dissolve the alumina crystals in the ZTA ceramic, providing "free oxygen" to the alumina, causing it to transform from an "alumina octahedral" structure to an "alumina tetrahedral" structure and enter the ZTA ceramic sintering aid. However, the solubility of alumina in the ZTA ceramic sintering aid is limited. During the holding period of sintering, some alumina dissolves in the intergranular ZTA ceramic sintering aid, while some alumina precipitates in the form of alumina crystals at sites conducive to nucleation. The dissolution and precipitation effect of the sintering aid on alumina is beneficial to the sintering of alumina ceramic crystals. Similarly, because the sintering aid contains a certain amount of phosphorus pentoxide, which exists in a layered structure in the glass network and has strong chemical activity, it promotes the dissolution of zirconia grains in ZTA ceramics. Zirconia also undergoes a dissolution and leaching effect through the ZTA ceramic sintering aid, which is beneficial to the sintering of zirconia ceramic crystals.

[0016] ZTA ceramic sintering aid introduces a certain amount of F through calcium fluoride. - F - As a monovalent anion, it enters the network structure of ZTA ceramic sintering aid and locally substitutes O. 2-This will greatly disrupt the integrity of the sintering aid network structure, significantly lower the diffusion barrier of cations in the sintering aid, and improve the diffusion capacity of cations in the sintering aid. The sintering aid introduces bismuth element through bismuth trioxide, with an atomic radius of 155 pm, very close to the 160 pm of zirconium atoms. During sintering, some bismuth atoms will diffuse to replace zirconium atoms in the ZTA ceramic crystal, increasing the lattice energy of the ZTA ceramic and improving its sintering activity. Simultaneously, the sintering aid introduces antimony element through antimony trioxide, with an atomic radius of 141 pm, very close to the 143 pm of aluminum atoms. During sintering, some antimony atoms will diffuse to replace aluminum atoms in the ZTA ceramic crystal, entering the ZTA ceramic lattice and improving its sintering activity.

[0017] Under the process of this invention, during the sintering of ZTA ceramics, on the one hand, some cations in the sintering aid enter the ZTA ceramic grain lattice through the substitution effect, improving the sintering activity of ZTA ceramics; on the other hand, through the melting and desorption effect, some alumina and zirconium oxide components in ZTA ceramics dissolve in the viscous ZTA ceramic sintering aid while simultaneously precipitating alumina and zirconium oxide crystals at easily precipitated locations, achieving rapid diffusion of alumina and zirconium oxide and promoting rapid densification of ZTA ceramics at low sintering temperatures.

[0018] The beneficial effect of this invention is that by adding a small amount of special ZTA ceramic sintering aid to the ZTA ceramic raw material, the ZTA ceramic can achieve dense sintering at 1250-1300℃. After sintering, the main crystalline phase in the ZTA ceramic is the same as that of the traditional ZTA ceramic after high-temperature sintering without the sintering aid, which is α-Al2O3 phase and tetragonal zirconium oxide (…). t -ZrO2) phase and monoclinic zirconium oxide ( m The -ZrO2) phase does not produce other impurity phases (see [link]). Figure 2 The ZTA ceramics prepared by this process achieved a density of 97.8% after sintering at 1250℃, which is roughly equivalent to the density of traditional ZTA ceramics sintered at 1650℃ without sintering aids (97.3%). See also... Figure 3 , Figure 4 , Figure 5 The five samples achieved a three-point flexural strength of 478 MPa, which is slightly higher than the average flexural strength of 452 MPa of traditional ZTA ceramics sintered at 1650 °C without sintering aids. This invention can obtain ZTA ceramic materials with density and flexural strength comparable to traditional ZTA ceramics sintered at 1650 °C at a lower temperature, thereby reducing the sintering cost of ZTA ceramic materials. Attached Figure Description

[0019] Figure 1 XRD pattern of ZTA ceramic sintering aid after melting at 1500℃.

[0020] Figure 2 Diffraction patterns of ZTA ceramics prepared by different processes.

[0021] 1# Traditional ZTA ceramic sample sintered at 1650℃ without sintering aid; 2# ZTA ceramic sample sintered at 1250℃ with 3wt% sintering aid.

[0022] Figure 3 Morphology of conventional ZTA ceramics containing 20wt% zirconium oxide without sintering aid after sintering at 1250℃.

[0023] Figure 4 Morphology of conventional ZTA ceramics containing 20wt% zirconium oxide without sintering aid after sintering at 1650℃.

[0024] Figure 5 The morphology of ZTA ceramics prepared by the process in Example 1 of this invention after sintering at 1250℃. Detailed Implementation

[0025] The present invention will be further described below with reference to the embodiments.

[0026] Example 1 A method for preparing zirconia-toughened alumina (ZTA) ceramics by low-temperature sintering, comprising the following specific steps: S1: Preparation of ZTA ceramic sintering aid S11: ZTA ceramic sintering aid is prepared by high-temperature melting method, and its weight percentage formula is as follows: Boric acid (chemically pure) 12% Sodium carbonate (chemically pure) 9% Potassium carbonate (chemically pure) 5% Calcium fluoride (chemically pure) 2% Bismuth trioxide (chemically pure) 7% Ammonium dihydrogen phosphate (chemically pure) 5% Antimony trioxide (chemically pure) 6% Silica (chemically pure) 54% The total is 100%.

[0027] S12: Pour the weighed raw materials into a corundum ball mill jar with a diameter of 400 mm. Add zirconia balls with a diameter of 30 mm at a ball-to-material mass ratio of 2:1. The rotation speed of the ball mill jar is 80 r / min. After ball milling the raw materials for 60 minutes, remove them to obtain ZTA ceramic sintering aid smelting raw materials.

[0028] S13: Heat the platinum crucible furnace to 1050℃ at a rate of 4℃ / min, plug the furnace with a stopper, pour in the mixed smelting raw material powder, and hold the furnace at 1000℃ for 1 hour. Then, heat the furnace to 1500℃ at a rate of 3℃ / min and hold for 2 hours. Place a heat-resistant steel container filled with water at the furnace outlet. Lift the stopper to allow the molten glass to flow into the water for water quenching. Collect the water-quenched glass fragments and place them in a planetary ball mill. Use ethanol as the dispersion medium and 5mm zirconia balls as the grinding medium. The mass ratio of glass fragments to ethanol to zirconia balls is 1:0.8:2. The milling speed is 800 r / min. After 12 hours of ball milling, pour out the slurry, dry it at 80℃, and then pass the glass powder through a 400# sieve to obtain ZTA ceramic sintering aid.

[0029] S2: Preparation of ZTA ceramic dry pressing material S21: The weight percentage formula of ZTA ceramic dry-pressed material is as follows: Alumina micro powder (diameter 1-5μm) 77% Yttrium-stabilized zirconia microparticles (diameter 1-5 μm) 20% ZTA ceramic sintering aid 3% S22: Weigh each raw material according to the formula ratio, use ethanol as solvent and 1mm ZrO2 grinding balls as grinding media, mix in a planetary ball mill at a speed of 800r / min for 3 hours, with the mass ratio of ethanol:ball:material being 1:1:1. After ball milling, dry the powder, then add 6wt% of the powder mass of PVA aqueous solution (10wt% solid content), mix in an S-type mixer for 2 hours, with the stirring paddle speed being 20-40r / min. After the mixed powder is sealed in a sealed bag and left for 24 hours, pass it through an 80# sieve to obtain ZTA ceramic dry-pressed material.

[0030] S3: Forming and Drying of ZTA Ceramics Select the corresponding mold according to the product specifications, weigh the corresponding mass of ZTA ceramic molding material, put it into the mold, press it into shape, when the molding reaches 120MPa, hold the pressure for 3 minutes, release the pressure, demold, place the molded ZTA ceramic blank on the SiC plate, place it at room temperature for 24 hours, and then put it in a 70℃ oven to dry for 12 hours.

[0031] S4: Sintering of ZTA ceramics Place the ZTA ceramic plate into the sintering furnace, heat it to 400℃ at a rate of 3℃ / min, hold for 1 hour, then heat it to 500℃ at a rate of 1℃ / min, hold for 1 hour, then heat it to 1100℃ at a rate of 4℃ / min, hold for 1 hour, then heat it to 1250℃ at a rate of 3℃ / min, hold for 3 hours, and then turn off the furnace. The ZTA ceramic is then allowed to cool naturally in the furnace. When the temperature is below 70℃, the ZTA ceramic is removed from the furnace to obtain the sintered ZTA ceramic product.

[0032] Figure 1 The diffraction pattern of the ZTA ceramic sintering aid is wave-shaped, with no crystal diffraction peaks observed, indicating that the sintering aid after melting is a glass phase.

[0033] Figure 2 This indicates that the main crystalline phase of the ZTA ceramic prepared by the process of the present invention after sintering at 1250℃ is the same as that of the conventional ZTA ceramic after sintering at 1650℃ without sintering aid.

[0034] Figure 3 This indicates that after traditional ZTA ceramics without sintering aids are sintered at 1250℃, the ceramic grains do not exhibit secondary grain growth, and the microstructure contains a large number of pores, failing to achieve dense sintering.

[0035] Figure 4 This indicates that after traditional ZTA ceramics without sintering aids are sintered at 1650℃, the ceramic grains exhibit significant secondary grain growth, and there are no pores in the microstructure, thus achieving dense sintering.

[0036] Figure 5 This indicates that the ZTA ceramics prepared by the process of this invention, after sintering at 1250℃, exhibit significant secondary grain growth, and the microstructure lacks pores. Its microstructure is consistent with... Figure 4 Traditional ZTA ceramics without sintering aids, after sintering at 1650℃, exhibit similar morphology to ZTA ceramics, achieving dense sintering.

Claims

1. A method for preparing zirconia-toughened alumina (ZTA) ceramics by low-temperature sintering, characterized in that, Includes the following steps: S1: Preparation of ZTA ceramic sintering aid S11: ZTA ceramic sintering aid, its raw material weight percentage formula is as follows: Boric acid 10%-15% Sodium carbonate 8-12% Potassium carbonate 4-6% Calcium fluoride 2-3% Bismuth trioxide 6-8% 4-5% ammonium dihydrogen phosphate Antimony trioxide 5-7% 48%-59% silica The total of all raw materials in the formula is 100%; S12: Ball mill the weighed raw materials to obtain ZTA ceramic sintering aid smelting raw materials; S13: Heat the ZTA ceramic sintering aid raw material to 1500-1550℃ and hold it at that temperature, then quench it in water, ball mill it, and sieve it to obtain the ZTA ceramic sintering aid; S2: Preparation of ZTA ceramic dry-pressed material S21: ZTA ceramic dry pressing material, its raw material weight percentage formula is as follows: Alumina micro powder 60%-90% Yttrium-stabilized zirconia micro powder 5%-38% ZTA ceramic sintering aid 2%-5% The total of all raw materials in the formula is 100%; S22: Weigh each raw material according to the formula ratio, ball mill it to obtain powder, add binder and mix to obtain ZTA ceramic dry pressing material; S3: Forming and Drying of ZTA Ceramics ZTA ceramic dry-pressed material is placed in a mold, pressed into a blank, and then dried; S4: Sintering of ZTA ceramics ZTA ceramic blanks are obtained by sintering at 1200-1300℃.

2. The method for preparing zirconia-toughened alumina (ZTA) ceramics by low-temperature sintering according to claim 1, characterized in that, In step S11, the ZTA ceramic sintering aid has the following raw material weight percentage formulation: Boric acid 10%-15% Sodium carbonate 9% Potassium carbonate 5% Calcium fluoride 2-3% Bismuth trioxide 6-8% 4-5% ammonium dihydrogen phosphate Antimony trioxide 5-7% 48%-59% silica.

3. The method for preparing zirconia-toughened alumina (ZTA) ceramics by low-temperature sintering according to claim 1, characterized in that, S12 includes the following steps; Pour the weighed raw materials into a corundum ball milling jar, add zirconia balls with a diameter of 30 mm at a ball-to-material mass ratio of 1-3:1, and set the ball milling jar to rotate at a speed of 60-100 r / min. After milling the raw materials for 60-120 min, remove them to obtain ZTA ceramic sintering aid smelting raw materials.

4. The method for preparing zirconia-toughened alumina (ZTA) ceramics by low-temperature sintering according to claim 1, characterized in that, S13 includes the following steps: The platinum crucible furnace is heated to 1000-1050℃ at a rate of 3-4℃ / min. The mixed smelting raw material powder is poured in. When the furnace temperature rises again to 900-1000℃, it is held for 0.5-1h. Then, the temperature is raised to 1500-1550℃ at a rate of 3-4℃ / min and held for 1-2h. The molten material is then allowed to flow into water for water quenching. The glass fragments after water quenching are collected and placed in a planetary ball mill for ball milling. After ball milling for 12-16h, the slurry is poured out, dried, and sieved to obtain ZTA ceramic sintering aid.

5. The method for preparing zirconia-toughened alumina (ZTA) ceramics by low-temperature sintering according to claim 1, characterized in that, In step S21, the weight percentage formula of ZTA ceramic dry pressing material is as follows: Alumina micro powder diameter 1-5μm 60%-90% Yttrium-stabilized zirconia micropowder, diameter 1-5 μm, 5%-38% ZTA ceramic sintering aid 2%-5%.

6. The method for preparing zirconia-toughened alumina (ZTA) ceramics by low-temperature sintering according to claim 1, characterized in that, S22 includes the following steps: After weighing each raw material according to the formula ratio, use ethanol as solvent and ZrO2 grinding balls as grinding media to mix the materials in a planetary ball mill for 1-3 hours. After ball milling, dry the powder and then add 5-7 wt% of the powder mass of the binder polyvinyl alcohol (PVA) aqueous solution. Mix for 1-2 hours. After the mixed powder is sealed in a sealed bag and left for 24-48 hours, it is sieved to obtain ZTA ceramic dry pressing material.

7. The method for preparing zirconia-toughened alumina (ZTA) ceramics by low-temperature sintering according to claim 1, characterized in that, S3 includes the following steps: Select a mold, weigh out ZTA ceramic dry pressing material, put it into the mold, apply pressure to form, when the forming pressure reaches 100-120MPa, hold the pressure for 2-3 minutes, release the pressure, demold, place the formed ZTA ceramic green body at room temperature for 24-48 hours, and then put it in an oven at 50-80℃ to dry for 6-24 hours.

8. The method for preparing zirconia-toughened alumina (ZTA) ceramics by low-temperature sintering according to claim 1, characterized in that, S4 includes the following steps: Place the ZTA ceramic blank in the sintering furnace and heat it to 400℃-450℃ at a rate of 2-3℃ / min, hold for 1-2 hours, then heat it to 500℃-550℃ at a rate of 1-2℃ / min, hold for 1-2 hours, then heat it to 1050℃-1100℃ at a rate of 3-4℃ / min, hold for 0.5-1 hours, then heat it to 1200-1300℃ at a rate of 2-3℃ / min, hold for 2-6 hours, and then turn off the furnace. The ZTA ceramic is then allowed to cool naturally in the furnace. When the temperature is below 70℃, the ZTA ceramic is removed from the furnace to obtain the sintered ZTA ceramic product.

9. A ceramic product, characterized in that, The product is prepared by any one of the methods of claims 1-8.

Citation Information

Patent Citations

  • Lower-temperature sintered zirconia toughened alumina material and preparation method

    CN103922705A

  • Ceramic mobile-phone rear cover and preparation method thereof

    CN107673757A